2021
DOI: 10.1242/dev.197087
|View full text |Cite
|
Sign up to set email alerts
|

Nutrition and PI3K/Akt signaling are required for p38-dependent regeneration

Abstract: Regeneration after damage requires early signals to trigger the tissue repair machinery. Reactive oxygen species (ROS) act as early signals that are sensed by the MAP3 kinase Ask1, which in turn activates by phosphorylation the MAP kinases p38 and JNK. The sustained or high activation of these kinases can result in apoptosis, whereas short or low activation can promote regeneration. Using the Ask1-dependent regeneration program, we demonstrate in Drosophila wing that PI3K/Akt signaling is necessary for Ask1 to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 11 publications
(13 citation statements)
references
References 41 publications
1
11
0
Order By: Relevance
“…PI3K/Akt signaling is necessary for Ask1 to phosphorylate p38, and the phosphorylation of p38 during regeneration is nutrient sensitive. This finding distinguishes p38 and JNK function in the cells involved in tissue repair and regenerative growth (Esteban-Collado et al 2021 ), but the interaction between JNK and p38 is still elusive. As mentioned above, studies on the roles of JNK and p38 in insect regeneration have mainly focused on Drosophila imaginal discs; the functions of these proteins in other insect appendages are less clear.…”
Section: Internal Mechanisms Underlying Regenerationmentioning
confidence: 98%
See 1 more Smart Citation
“…PI3K/Akt signaling is necessary for Ask1 to phosphorylate p38, and the phosphorylation of p38 during regeneration is nutrient sensitive. This finding distinguishes p38 and JNK function in the cells involved in tissue repair and regenerative growth (Esteban-Collado et al 2021 ), but the interaction between JNK and p38 is still elusive. As mentioned above, studies on the roles of JNK and p38 in insect regeneration have mainly focused on Drosophila imaginal discs; the functions of these proteins in other insect appendages are less clear.…”
Section: Internal Mechanisms Underlying Regenerationmentioning
confidence: 98%
“…JNK and p38 are conserved subfamilies of mitogen-activated protein kinases (MAPKs) that sense and elicit cellular responses to stress and tissue damage (Roux and Blenis 2004 ). During wing disc regeneration, apoptotic signal-regulating kinase 1 (Ask1) and Akt kinase (Akt) sense ROS in both dying and living cells to activate moderate phosphorylation levels of p38 and JNK (Esteban-Collado et al 2021 ; Santabárbara-Ruiz et al 2019 ). Damage-induced JNK signaling leads to the upregulation of the Duox-maturation factor NIP, which in turn promotes ROS generation in regenerating tissue (Khan et al 2017 ).…”
Section: Internal Mechanisms Underlying Regenerationmentioning
confidence: 99%
“…Thus, it is conceivable that the mechanisms that sense the nutritional status of the organism are key in sensing damage and therefore in the onset of regeneration. Indeed, it has recently been found that nutrient restriction blocks regeneration in similar phenotypes such as downregulation of Pi3K/Akt or in the mutated Ser83 of Ask1 ( Santabárbara-Ruiz et al, 2019 ; Esteban-Collado et al, 2021 ). More importantly, it has also been found that the anomalous regeneration resulting from nutrient restriction or from mutated Ask1 Ser83 can be rescued by ectopic activation of p38, but not of JNK ( Esteban-Collado et al, 2021 ).…”
Section: How Is Damage Sensed?mentioning
confidence: 99%
“…Indeed, it has recently been found that nutrient restriction blocks regeneration in similar phenotypes such as downregulation of Pi3K/Akt or in the mutated Ser83 of Ask1 ( Santabárbara-Ruiz et al, 2019 ; Esteban-Collado et al, 2021 ). More importantly, it has also been found that the anomalous regeneration resulting from nutrient restriction or from mutated Ask1 Ser83 can be rescued by ectopic activation of p38, but not of JNK ( Esteban-Collado et al, 2021 ). These observations demonstrate that the function of Pi3K/Akt in regeneration is channelled through p38 rather than JNK.…”
Section: How Is Damage Sensed?mentioning
confidence: 99%
“…In Drosophila , Ask1 in the gut and imaginal epithelia operates as a survival signal in tissue regeneration by triggering a non-apoptotic function of p38 (Patel et al, 2019; Santabárbara-Ruiz et al, 2019). This is achieved by a ROS-dependent, Akt-induced phosphorylation of Ser83 in Ask1 (Ser174 in humans) that is essential to redirect the Ask1 signaling pathway towards p38 and thus drive regeneration (Esteban-Collado et al, 2021).…”
Section: Introductionmentioning
confidence: 99%

ROS-mediated TNFR Wengen activation in response to apoptosis

Esteban-Collado,
Fernàndez-Mañas,
Fernández-Moreno
et al. 2023
Preprint
Self Cite